A Survey on Mobile Learning for Adult Learners: State-of-the-Art, Taxonomy, and Challenges - Shima Sabri; Abdullah Gani; Elaheh Yadegaridehkordi; Christopher Ifeanyi Eke; Liyana Shuib (IEEE Access, 2022)
Adult learner performance has become a significant challenge in education. Adult learners are identified as being of productive age in engaging with multiple commitments, including studying. The multiple engagements make managing their time and focus difficult, contributing to a high institutional dropout rate. This situation has reduced the number of highly skilled and professional workers in the country because of the failure to meet academic requirements. In the current digital world, every aspect of education includes some technology elements. However, most adult learners are reluctant to utilize mobile technology for learning. Therefore, this review paper aims to provide state of the art on mobile learning (m-Learning) for adult learners. Considering a set of inclusion and exclusion criteria, 135 related articles from IEEE, Google Scholar, Springer Link, Science Direct, Taylor and Francis, and Wiley digital databases were extracted and reviewed. State of the art were discussed in terms of functions of m-Learning, effectiveness, and m-Learning as a tool. Keywords from articles were extracted and the taxonomy of m-Learning was discussed under five classifications (behavioural intention, technological support, educational content, learner coordination, and instructional design), representing the same meaning and features discussed in the articles. The findings can raise awareness among mobile learning practitioners to provide more effective services for adult learners. Meanwhile, higher education institutions can be better redesigned in terms of pedagogy to fit the needs of adult learners with mobile learning.